Effect of elevated temperature to radiation shielding of ultra-high performance concrete with silica sand or magnetite - Muhammad Rashid, Raizal Saifulnaz; S., Mohammed Salem; N. M., Azreen; Y. L., Voo; M., Haniza; A. A., Shukri; Yahya, Mohd Syukri (Elsevier, 2020)
The high density and strength of ultra-high performance concrete (UHPC) makes it suitable for radiation shielding, however, the deterioration of radiation shielding properties due to exposure to elevated temperature is a major concern. Hence this paper presents a study on the radiation shielding properties of UHPC after exposure to elevated temperature. It was found that the half-value layer and tenth value layer of both types of UHPC tested had increased by 76–82%, which was attributed to the excessive spalling and cracking that occurred. Magnetite was found to be slightly better than silica sand for radiation shielding.